2007
DOI: 10.5039/agraria.v2i4a1928
|View full text |Cite
|
Sign up to set email alerts
|

Sorção do Paclobutrazol em dois solos cultivados com manga irrigada

Abstract: A cinética e a isoterma de sorção do Paclobutrazol (PBZ) foram determinadas em dois solos com plantio de manga (Mangifera indica L. cv. Tommy Atkins) irrigada, sem histórico de aplicação deste produto, ou seja, um Argissolo Amarelo da estação experimental de Bebedouro, Petrolina, PE, e outro Vertissolo da estação experimental de Mandacaru, Juazeiro, BA, ambas pertencentes à EMBRA-PA Semi-Árido. Os ensaios foram realizados em laboratório a 25°C e a concentração de paclobutrazol determinada por cromatografia líq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Clay minerals and soil organic matter can weakly or strongly adsorb organic molecules, depending on the sorption mechanism and on adsorbent-adsorbate interaction forces (Milfont et al, 2007). Studies conducted in soils have confirmed that SMX is adsorbed by the organic matter and minerals of the clay fraction, but not by the sand fraction and gravels composing the soil, as observed by Hou et al (2010), who demonstrated that SMX has high sorption in organic fractions (humic acids) and in mineral inorganic particles, but low sorption in the particles of the original sediments of a soil.…”
Section: Resultsmentioning
confidence: 99%
“…Clay minerals and soil organic matter can weakly or strongly adsorb organic molecules, depending on the sorption mechanism and on adsorbent-adsorbate interaction forces (Milfont et al, 2007). Studies conducted in soils have confirmed that SMX is adsorbed by the organic matter and minerals of the clay fraction, but not by the sand fraction and gravels composing the soil, as observed by Hou et al (2010), who demonstrated that SMX has high sorption in organic fractions (humic acids) and in mineral inorganic particles, but low sorption in the particles of the original sediments of a soil.…”
Section: Resultsmentioning
confidence: 99%